Clinicopathological aspects of adenocarcinoma of the large bowel in a low incidence population. Issue 3 (19th November 2013) - Dakubo, Jonathan C.B.; Naaeder, Simon S.B.; Gyasi, Richard K.
<x xml:space="preserve">Abstract</x> Background and Objectives The presentation of the different histopathologic subtypes of adenocarcinoma of the large bowel vary within the colorectum and appears to impact on treatment. This study evaluated the relationships between the clinical features of adenocarcinoma of the large bowel, the histopathologic subtypes, and treatment. Methods Patients with adenocarcinoma of the large bowel presenting to the Korle Bu Teaching Hospital from January 1997 to December 2011 were studied. Results The study involved 579 patients: 310 (53.5%) males and 269 (46.5%) females, median age 58 years. Right colon cancers were 170 (29.4%), left colon 128 (22.1%), and rectum 281 (48.5%). Well‐differentiated cancers were 254 (43.3%), moderately differentiated 178 (30.3%), mucinous 90 (14.8%), anaplastic 44 (7.5%), and signet‐ring cell cancer 13 (2.2%). The mean ages across the histologic types were unequal, F‐test 8.34, P‐value 0.0005, with patients with mucinous and signet‐ring cancers much younger. Mucinous cancers were predominantly in the right colon while signet‐ring cell cancers were mostly in the rectum. Well‐ and moderately differentiated cancers presented at early stage than anaplastic and signet‐ring cell cancers, P ∼ 0.01 and P < 0.03, respectively. The overall resection rate was 346 (59.8%) with rectal cancer having very low resection rate of 81 (28.8%). Conclusion Adenocarcinoma of the large bowel was predominantly in the rectum and in patients who were 50 years and older and were mostly well or moderately differentiated cancers. J. Surg. Oncol. 2014 109:245–249. © 2013 Wiley Periodicals, Inc.